Effects of operational control conditions on the seasonal energy storage performance of borehole thermal energy storage (BTES) system - Weibo Yang; Wenxin Xia; Yu Zhang; Feng Wang (Case Studies in Thermal Engineering, 2025)
To explore the effects of operation control conditions on the seasonal energy storage performance of borehole thermal energy storage (BTES) system, a three-dimensional model of the BTES is built and validated by experiments. The effects of different inlet temperatures, inlet flow rates and methods of controlling on the energy storage body temperature and energy storage characteristics of the BTES are examined. As the findings indicate that, for optimal energy utilization, selecting excessively high inlet temperatures for heat storage is not advisable. For this study, the energy storage efficiency and exergy efficiency are lowest when the heat storage inlet temperature is 50 °C. For the same heat storage temperature, lower inlet temperatures for heat extraction result in higher energy storage and exergy efficiency. For the current simulation conditions, when the heat extraction temperature is 5 °C, the energy storage efficiency and exergy efficiency are the highest, and the heat extraction is also the most. The intermittent operation reduces the heat storage and extraction capacity, but increases the efficiency of the energy storage system. In terms of energy storage characteristics, the inlet flow rate has a lesser impact than the inlet temperature. Increasing the inlet flow rate does not significantly enhance the heat storage and extraction capacity. Furthermore, there is a critical point beyond which the energy storage and exergy efficiencies no longer improve with higher flow rates. For example, when the flow rate increases from 0.2 to 0.6 m/s, the energy storage efficiency and exergy efficiency increase with the rise of the inlet flow rate. However, when the flow rate increases to 0.8 m/s, the energy storage efficiency and exergy efficiency decrease. Thus, the inlet flow rate should be optimized based on the specific operating conditions of the system. Among the four zoning operation strategies, the combination of heat storage and extraction in mode 4 is the most unfavorable. It has the lowest energy storage efficiency and exergy efficiency, and the least heat extraction capacity. However, when considering energy storage and exergy efficiency, the mode 4 with non-uniform heat storage and extraction intensities outperforms the other three non-uniform strategies. These findings provide valuable insights for optimizing the operation of BTES systems, ensuring more efficient energy storage and extraction.